(untitled) (World Economics and Finance Bulletin, 2023)
The research aimed to identify the relationship of cash and investment flows in the returns of stocks in the Iraq Stock Exchange. The research problem was represented by the extent to which investors depend on the indicators shown in the list of flows and rely on them when investing. The research started from the hypothesis that there is a positive and significant relationship between the indicators of cash and investment flows in Stock returns, and for the purpose of verifying the validity of the hypothesis from which the research was launched, data on cash flows were collected from 6 industrial companies operating in the Iraq Stock Exchange.